ظاهرة انتشار الأحاديث المردودة بين المجتمع الماليزي: أسباب وحلول - Nur Afifi bin Alit; Shumsudin Yabi (Kolej Universiti Islam Antarabangsa Sultan Ismail Petra (KIAS), 2024)
The dissemination of rejected hadith has been a continuous challenge since the emergence of hadith literature in the 19th century. There are several reasons behind this phenomenon which, if not treated seriously, can hinder the search for appropriate solutions because Muslims depend highly on these hadith in their daily worship. Therefore, this study is conducted to identify the cause of this phenomenon and find an appropriate solution. The methods used in this qualitative study are document analysis, supported by observations of the occurring phenomena, and the documents gathered are later analyzed using the descriptive method. This study found external and internal causes that assisted in spreading these hadith in society, pointing to two main parties as the spreaders of hadith: the preachers and the intellectuals. In addition, this study also suggests taking advantage of the enhancement of technology, like television programs and mobile applications, to educate society on hadith knowledge and the difference between accepted and rejected hadith. Finally, it is also suggested that all parties and bodies in Malaysia related to this matter should be gathered to address this issue with their best foot forward to achieve the best solutions.